Characterizing the cellular immune response to subretinal AAV gene therapy in the murine retina - Laurel C. Chandler; Michelle E. McClements; Imran H. Yusuf; Cristina Martinez-Fernandez de la Camara; Robert E. MacLaren; Kanmin Xue (Molecular Therapy: Methods & Clinical Development, 2021)
Although adeno-associated viral (AAV) vector-mediated retinal gene therapies have demonstrated efficacy, the mechanisms underlying dose-dependent retinal inflammation remain poorly understood. Here, we present a quantitative analysis of cellular immune response to subretinal AAV gene therapy in mice using multicolor flow cytometry with a panel of key immune cell markers. A significant increase in CD45+ retinal leukocytes was detected from day 14 post-subretinal injection of an AAV8 vector (1 × 109 genome copies) encoding green fluorescent protein (GFP) driven by a ubiquitous promoter. These predominantly consisted of infiltrating peripheral leukocytes including macrophages, natural killer cells, CD4 and CD8 T cells, and natural killer T cells; no significant change in resident microglia population was detected. This cellular response was persistent at 28 days and suggestive of type 1 cell-mediated effector immunity. High levels (80%) of GFP fluorescence were found in the microglia, implicating their role in viral antigen presentation and peripheral leukocyte recruitment. When compared against AAV.GFP in paired eyes, an equivalent dose of an otherwise identical vector encoding the human therapeutic transgene Rab-escort protein 1 (REP1) elicited a significantly diminished cellular immune response (4.2-fold; p = 0.0221). However, the distribution of immune cell populations remained similar, indicating a common mechanism of AAV-induced immune activation.